Self-repairing abrasion-resistant concrete based on heat-shrinkable fiber net and electromagnetic induction self-repairing fiber and preparation method of self-repairing abrasion-resistant concrete

By combining cross-linked modified heat-shrink fiber mesh and electromagnetic induction self-repair fibers in impact-resistant concrete, the quality defects and environmental sensitivity problems of impact-resistant concrete during construction are solved, and the efficient self-repair and durability of concrete are achieved. Sex improvement.

CN119390378AActive Publication Date: 2025-02-07WUHAN UNIV OF TECH
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411520333.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-07
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

Existing impact-resistant concrete is prone to quality defects during construction and is sensitive to environmental conditions. Changes in temperature and humidity will affect its performance. The effect of traditional restoration methods is unstable, making it difficult to effectively solve concrete cracks and durability problems.

Method used

The self-repair impact-resistant concrete based on heat shrink fiber mesh and electromagnetic induction self-repair fiber is adopted. The stability, load-bearing capacity and impact-resistant concrete are improved by combining cross-linked modified heat shrink fiber mesh and electromagnetic induction self-repair fiber. performance and realize self-repair of concrete cracks.

Benefits of technology

It significantly improves the durability and service life of concrete, enhances impact wear performance and integrity, can better resist erosion by environmental factors, delay the deterioration process, and achieve rapid self-repair.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses self-repairing abrasion-resistant concrete based on a heat-shrinkable fiber net and electromagnetic induction self-repairing fibers. The self-repairing abrasion-resistant concrete comprises an abrasion-resistant concrete base body, a cross-linked modified heat-shrinkable fiber net and the electromagnetic induction self-repairing fibers, wherein the cross-linked modified heat-shrinkable fiber net and the electromagnetic induction self-repairing fibers are distributed in the abrasion-resistant concrete base body; wherein the cross-linking modified thermal shrinkage fiber net is a fiber net which is formed by weaving polyester fibers and aramid fibers in sequence and is subjected to cross-linking modification; the electromagnetic induction self-repairing fiber comprises a core material and a wall material, the core material comprises methyl methacrylate and butyl acrylate, and the wall material comprises polylactic acid and nano Fe3O4. According to the invention, the cross-linked and modified heat-shrinkable fiber net is combined with an electromagnetic induction self-repairing fiber technology, so that the stability, the bearing capacity and the abrasion resistance of the concrete can be effectively improved, the controllable self-repairing of concrete cracks is realized, the durability of the concrete is remarkably improved, the service life of the concrete is remarkably prolonged, and the like. A new thought can be provided for preparation of the high-performance abrasion-resistant concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and in particular relates to a self-repairing anti-abrasion concrete based on a heat-shrinkable fiber net and an electromagnetic induction self-repairing fiber, and a preparation method thereof. Background Art

[0002] Abrasion-resistant concrete usually uses high-performance aggregates, special cements and additives, which can significantly improve the physical and mechanical properties of concrete. This type of concrete has high compressive strength and flexural strength, as well as good impact resistance and wear resistance. Its application scenarios include airport runways, port terminals, industrial floors, etc. However, abrasion-resistant concrete is prone to quality defects during the construction process, such as delamination and floating; furthermore, it is sensitive to environmental conditions, and changes in temperature and humidity can affect its performance. Cracks are common in concrete structures (which may be caused by shrinkage, temperature changes, or load deformation, etc.), which can reduce structural strength and durability, affecting safety and service life. Traditional repair methods such as drilling and grouting and surface coating repairs have limitations such as unstable effects, complex operations, and time-consuming.

[0003] Fiber-reinforced concrete (FRC) is a composite material that improves its toughness and crack resistance by adding various types of fibers to concrete. However, a single fiber mainly provides local reinforcement by evenly distributing the fibers in concrete, which only improves microcracks and local areas and cannot cope with large structures with high loads and high stresses. Concrete composites composed of high-performance fiber woven mesh and concrete matrix have excellent mechanical properties, good durability and light weight. They can be used for building structure reinforcement and new building structures, but there are still the following problems and shortcomings: the fiber mesh alone is difficult to cope with the expansion of concrete cracks, and the ability to repair and toughen larger cracks is limited; if the surface treatment technology is not perfect, it will also lead to insufficient bonding with the matrix material, resulting in debonding and other phenomena. Heat-shrinkable fiber technology also has certain applications in concrete, but it mainly works at a specific temperature. For actual engineering environments with small temperature changes, the heat-shrinkability is difficult to fully demonstrate; in addition, the effect of chopped heat-shrinkable fibers on improving the durability of concrete is not significant, and it cannot effectively solve the corrosion and aging problems that concrete has long faced.

[0004] Microcapsule technology is to add microcapsules containing repair agents into cement-based materials. When cracks appear, the capsules rupture to release the repair agents, fill the cracks, and prevent the cracks from expanding, thereby improving the durability and service life of the materials. Although it can achieve a certain degree of self-repair, there are usually problems such as low strength and easy breakage of wall materials, high selectivity and difficulty in controlling the activity of core materials, and uncontrollable or limited control effects of the release process of repair materials, which affect the self-repair effect. In addition, simple self-repairing microcapsules have limited improvement on the overall mechanical properties of concrete and cannot meet the engineering requirements for high strength and impact resistance. Summary of the invention

[0005] The main purpose of the present invention is to address the problems and shortcomings of the prior art and to provide a self-repairing and abrasion-resistant concrete based on heat-shrinkable fiber mesh and electromagnetic induction self-repairing fiber. The combination of cross-linked modified heat-shrinkable fiber mesh and electromagnetic induction self-repairing fiber technology can effectively improve the stability, bearing capacity and abrasion resistance of concrete, and realize self-repair of concrete cracks, which can significantly improve the durability and service life of concrete, etc., and has a wide range of applicability.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] A self-repairing anti-impact concrete based on a heat-shrinkable fiber net and an electromagnetic induction self-repairing fiber, comprising an anti-impact concrete matrix and a cross-linked modified heat-shrinkable fiber net and an electromagnetic induction self-repairing fiber distributed therein; wherein the cross-linked modified heat-shrinkable fiber net is a fiber net in which polyester fiber and aramid fiber are woven and cross-linked in sequence; the electromagnetic induction self-repairing fiber comprises a core material and a wall material, wherein the core material comprises methyl methacrylate (MMA) and butyl acrylate (BA), and the wall material comprises polylactic acid (PLA) and nano-Fe 3 O 4 .

[0008] In the above scheme, the raw materials of the self-repairing and abrasion-resistant concrete and their weight proportions include: 1008-1140 parts of raw materials used for the abrasion-resistant concrete matrix, 12-44 parts of electromagnetic induction self-repairing fibers, and 50-70 parts of cross-linked modified heat shrinkable fiber mesh.

[0009] Furthermore, the raw materials of the anti-abrasion concrete matrix and their weight proportions include: 400 parts of silicate cement, 78-110 parts of silica fume, 350-400 parts of fine sand, 70-90 parts of steel fiber, 15-20 parts of water reducer, and 95-120 parts of water.

[0010] Furthermore, the electromagnetic induction self-repairing fibers account for 3-11% of the mass of the cement.

[0011] In the above solution, the heat shrinkable fiber mesh is woven into a mesh using a process such as a plain weave method.

[0012] In the above scheme, the cross-linking modification step includes: soaking the blended web of polyester fiber and aramid fiber in a divinylbenzene cross-linking agent solution, cross-linking reaction, removing the fiber web, and drying to obtain a cross-linked modified fiber web.

[0013] Furthermore, in the divinylbenzene crosslinking agent solution, the concentration of divinylbenzene is 10-15 wt %; the solvent used is cyclohexane, toluene or xylene.

[0014] In the above scheme, the cross-linking reaction time is 2 to 3 hours.

[0015] In the above scheme, the drying temperature is 90-100° C. and the time is 2-4 hours.

[0016] In the above scheme, the stirring speed to obtain the cross-linking solution is 300 to 500 r / min, and the time is 15 to 30 min.

[0017] In the above scheme, the pore size of the obtained heat shrinkable fiber mesh is 500-1000 μm, and the fiber diameter is 3-20 μm.

[0018] Furthermore, the blending ratio (mass ratio) of the polyester fiber and the aramid fiber is 1:2 to 2:1.

[0019] In the above scheme, the average diameter of the electromagnetic induction self-repairing fiber is 0.2-2 μm, the average thickness of the capsule wall is 50-300 nm; and the length of the electromagnetic induction self-repairing fiber is 250-4000 μm.

[0020] Furthermore, the aspect ratio of the electromagnetic induction self-healing fiber is 500-2000.

[0021] Furthermore, the added amount of the electromagnetic induction self-repairing fiber accounts for 3-11% of the mass of the cement.

[0022] In the above scheme, the method for preparing the electromagnetic induction self-repairing fiber comprises the following steps:

[0023] 1) Preparation of core material: weigh methyl methacrylate, butyl acrylate, a crosslinking agent and an initiator according to a ratio; stir the weighed methyl methacrylate and butyl acrylate evenly (stir at room temperature for 10 to 15 minutes), then add divinylbenzene and azobisisobutyronitrile, and stir for 30 to 40 minutes to obtain a composite core material;

[0024] 2) Preparation of spinning solution: prepare polylactic acid solution (the solvent can be chloroform, etc.), add the obtained composite core material thereto, stir evenly, add tributyl citrate and stir evenly (stir for 10 to 15 minutes), then add ferrosoferric oxide nanoparticles, and disperse by ultrasonication (30 to 40 minutes) to obtain a spinning solution containing core material, wall material and magnetic material;

[0025] 3) Electrospinning: The prepared spinning solution is subjected to electrospinning to form fibrous microcapsules.

[0026] In the above scheme, methyl methacrylate (MMA) is used as the main repair agent, accounting for 70-80% of the total mass of the core material; butyl acrylate (BA) is used as an auxiliary repair agent to adjust the core material performance, accounting for 20-30% of the total mass of the core material.

[0027] In the above scheme, the crosslinking agent can be divinylbenzene (DVB) or the like, accounting for 5-10% of the total mass of the core material; the initiator can be azobisisobutyronitrile (AIBN) or the like, accounting for 1-3% of the total mass of the core material.

[0028] In the above scheme, in the polylactic acid solution, the concentration of polylactic acid is 0.15-0.25 g / mL; and an organic solvent such as chloroform is used.

[0029] In the above scheme, in the obtained spinning solution, the volume percentage of the solvent is 70-80%; the mass percentage of tributyl citrate is 5-10%; and the mass percentage of ferrosoferric oxide nanoparticles is 3-5%.

[0030] In the above scheme, the process parameters adopted in the electrospinning step include: the distance between the needle and the receiving device is 15-25 cm, the set voltage is 15-25 kV, the spinning speed is 0.5-1.5 mL / h, the spinning process lasts 2-3 hours, and the spinning fiber length is set to 250-4000 μm to obtain electromagnetic induction self-healing fiber.

[0031] Furthermore, the silicate cement is one of P·I 52.5 grade and P·II 52.5 grade.

[0032] Furthermore, the SiO 2 The content of silica fume is ≥92%, and the particle size of the silica fume is 0.1-0.3 μm.

[0033] Furthermore, the fine sand is one of natural sand and quartz sand, and the particle size of the fine sand is 0.075-0.6 mm.

[0034] Furthermore, the steel fiber is a copper-plated steel fiber; the length of the steel fiber is 12 to 13 mm, and the diameter is 0.18 to 0.23 mm.

[0035] Furthermore, the water reducing agent is a polycarboxylic acid water reducing agent, and the water reducing rate is ≥25%.

[0036] The above-mentioned method for preparing the self-repairing anti-abrasion concrete based on the heat-shrinkable fiber net and the fibrous electromagnetic induction microcapsules comprises the following steps:

[0037] 1) The cross-linked modified heat shrinkable fiber mesh is arranged in the middle of the mold according to the structural requirements of the impact-resistant concrete;

[0038] 2) preparing a slurry of an anti-impact concrete matrix according to a proportion, and then adding the electromagnetic induction self-repairing fiber into the obtained slurry and stirring it evenly;

[0039] 3) pouring the obtained mixture into a mold provided with a heat-shrinkable fiber mesh, forming, and curing to obtain the self-repairing anti-impact concrete.

[0040] In the above solution, the abrasion-resistant concrete is a cylindrical or block structure.

[0041] Furthermore, when preparing cylindrical impact-resistant concrete, the heat-shrinkable fiber mesh is in a hollow cylindrical shape and is arranged in a middle position coaxial with the cylindrical impact-resistant concrete; when preparing block impact-resistant concrete, the heat-shrinkable fiber mesh is in a planar mesh structure and is arranged in the middle position of the cylindrical impact-resistant concrete along the thickness direction parallel to the surface of the impact-resistant concrete.

[0042] Furthermore, when preparing cylindrical impact-resistant concrete, in the pouring process of step 3), the mixture is first poured into the hollow cylindrical heat-shrinkable fiber mesh, and after hardening and shaping, the remaining mixture is continued to be poured until the mold is filled.

[0043] In the above scheme, the abrasion-resistant concrete adopts a standard curing process.

[0044] The self-repairing anti-abrasion concrete prepared according to the above scheme has a compressive strength of 90.3-127.8MPa and an anti-abrasion strength of 97.2h / (kg / m 2 )~117.5h / (kg / m 2 ).

[0045] Compared with the prior art, the present invention has the following beneficial effects:

[0046] (1) The present invention uses polyester fiber and aramid fiber to prepare a heat-shrinkable fiber mesh. The cross-linked modified heat-shrinkable fiber mesh is beneficial to enhancing the bonding force between the fiber and concrete, and can effectively prevent the fiber from being pulled out during the impact and abrasion process, thereby improving the integrity of the concrete. Secondly, the heat release of cement hydration causes the heat-shrinkable fiber mesh to shrink in response, and generates pre-compression stress on the surrounding hardened gel slurry, thereby inhibiting the further expansion of microcracks. By dispersing these stresses, the heat-shrinkable fiber mesh can exhibit better ductility and impact resistance when subjected to impact or vibration, thereby preventing brittle failure. Moreover, after the heat shrinkage treatment, the fiber structure is made tighter, and a three-dimensional reinforcement network is formed in the concrete, which can absorb and disperse energy, prevent the generation and expansion of cracks, and improve crack resistance and toughness. The introduced fiber mesh can inhibit the generation of microcracks by shrinkage and enhance the impact and abrasion resistance. The above characteristics work together to significantly improve the durability of concrete, better resist environmental factors such as water scouring, chemical erosion, and alternating dry and wet conditions, prevent the entry of corrosive media, and delay the deterioration process. The heat-shrinkable fiber mesh can ensure the enhanced protection effect during long-term use and extend the service life of impact and abrasion-resistant concrete.

[0047] (2) The electromagnetic induction self-repairing fiber prepared by the present invention can trigger the release of the repair agent by applying a magnetic field when the concrete is damaged by impact and abrasion. At the same time, the heat-shrinkable fiber mesh shrinks in response to heat, which synergistically promotes the realization of the self-repairing function, significantly prolongs the service life of the concrete and improves its durability; it can also simultaneously enhance the integrity and toughness of the concrete, improve its impact and abrasion resistance, and the electromagnetic controlled release is controllable; the resulting fibrous structure has a large specific surface area, and the repair agent is released faster, thereby improving the repair efficiency; it can better combine with the cement matrix to form a uniformly reinforced network, thereby improving the mechanical properties and impact and abrasion resistance; it uses biodegradable polylactic acid as the wall material, which is environmentally friendly and has good long-term stability, avoids the problems of aging and degradation of traditional materials, and has good biocompatibility; the obtained electromagnetic induction self-repairing fiber has stable quality and performance, which is conducive to ensuring the stable release of the repair agent.

[0048] (3) The present invention combines heat-shrinkable fiber mesh and electromagnetic induction self-repairing fiber, which can significantly improve the durability and service life of concrete, effectively enhance the stability and bearing capacity of concrete and realize self-repair of concrete cracks. It has the advantages of high environmental adaptability and rapid repair, and is suitable for promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 This is a schematic diagram of the structure of the abrasion-resistant concrete according to Example 1 of the present invention;

[0050] Figure 2 Comparison of the self-repairing effects of cracks in impact-resistant concrete that incorporates both heat-shrinkable fiber mesh and electromagnetic induction self-repairing fiber: (a) before repair; (b) after repair. DETAILED DESCRIPTION

[0051] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0052] In the following embodiments, the heat shrinkable fiber mesh is woven from polyester fiber and aramid fiber using a plain weave method, and the modified preparation method includes the following steps:

[0053] 1. Weigh 10 g of divinylbenzene, slowly add it into 90 g of cyclohexane, and stir evenly with a stirrer (speed 400 r / min, time 25 min) to obtain a cross-linking solution;

[0054] 2. Immerse the blended web of polyester fiber and aramid fiber prepared by plain weaving method in the cross-linking solution for 2.5 hours. After the immersion, take out the fiber web and place it in a well-ventilated place to drain the excess solution; then put the fiber web into an oven (90°C, 3h) to obtain the heat-shrinkable fiber web.

[0055] In order to further verify the heat shrinkage performance of the fiber mesh described in the present invention, the obtained heat shrinkable fiber mesh was placed in a high-temperature furnace, and the temperature was increased to 100-180°C at a rate of 5-10°C / min and kept warm for 30 minutes to allow the fiber mesh to shrink. The pore size change results of the obtained fiber mesh are shown in Table 3.

[0056] Among them, the mechanical and physical property test results of the polyester fiber and aramid fiber used are shown in Table 1 and Table 2 respectively; among them, the tensile strength, Young's modulus and elongation are measured by quasi-static test; the performance test structure of the obtained heat shrinkable fiber mesh is shown in Table 3.

[0057] Table 1 Mechanical and physical properties of polyester fibers

[0058]

[0059] Table 2 Mechanical and physical properties of aramid

[0060]

[0061] Table 3 Changes in the aperture of heat shrinkable fiber mesh

[0062]

[0063] The method for preparing the electromagnetic induction self-repairing fiber comprises the following steps:

[0064] 1. Accurately weigh 80g of methyl methacrylate, 30g of butyl acrylate, 6.32g of divinylbenzene and 10g of azobisisobutyronitrile according to the mass ratio; put the weighed methyl methacrylate and butyl acrylate into a clean and dry three-necked flask, add a magnetic stirrer, turn on the magnetic stirrer, and stir at room temperature for 15min to fully mix them; slowly add divinylbenzene and azobisisobutyronitrile to the above mixed solution, continue stirring for 40min, ensure that all reagents are evenly mixed, and obtain a composite core material for standby use;

[0065] 2. Weigh 10.5 g of polylactic acid and put it into another clean and dry three-necked flask, measure 70 mL of chloroform and slowly add it into the three-necked flask, stir at 40 ° C for 1 hour, so that the polylactic acid is completely dissolved in the chloroform to form a polylactic acid solution with a concentration of 0.15 g / mL; add the composite core material (126.32 g) obtained in step 1 to the obtained polylactic acid solution, and continue to stir for 30 minutes to make it uniformly dispersed; according to the total mass of the spinning solution, weigh 5% of the total mass of the spinning solution, tributyl citrate (10.75 g), pour it into the three-necked flask, and stir for 15 minutes; weigh 3% of the total mass of the spinning solution. Ferroferric oxide nanoparticles (6.77 g) are poured into the three-necked flask; turn on the ultrasonic disperser, ultrasonically disperse for 35 minutes, so that the ferroferric oxide nanoparticles are evenly dispersed in the spinning solution, and a spinning solution containing core material @ wall material and magnetic material and good spinnability is obtained;

[0066] 3. Use a syringe to absorb the prepared spinning solution, and ensure that there are no bubbles inside the syringe and the needle; install the syringe on the electrospinning device, adjust the distance between the needle and the receiving device to 20 cm, set the voltage of the electrospinning device to 15 kV, and the spinning speed to 1.5 mL / h; turn on the electrospinning device, and under the action of the electrostatic field, the spinning solution is ejected from the needle to form spinning fibers on the receiving device. The spinning process lasts for 3 hours;

[0067] 4. The collected spun fibers were placed in a fume hood at room temperature for 48 hours to allow the chloroform and other organic solvents to fully evaporate, and then dried (in a vacuum drying oven at 50°C for 24 hours) to obtain dry electromagnetic induction self-healing fibers.

[0068] Table 4 Performance test results of electromagnetic induction self-repairing fibers

[0069]

[0070] In the following examples, the cement used is P·I 52.5 grade, the particle size of silica fume is 0.25 μm, the fine sand is natural sand, and its particle size is 0.075-0.6 mm. The steel fiber used is copper-plated steel fiber, and its length is 12-13 mm, and its diameter is 0.18-0.23 mm. The water reducer is a polycarboxylate water reducer, and its water reduction rate is 25%.

[0071] Example 1

[0072] A self-repairing anti-impact concrete based on a heat-shrinkable fiber net and an electromagnetic induction self-repairing fiber (the specimen is cylindrical), wherein the components and their weight proportions include: 1062 parts of self-repairing anti-impact concrete raw materials, 12 parts of electromagnetic induction self-repairing fibers, and 60 parts of cross-linked modified heat-shrinkable fiber nets; wherein the self-repairing anti-impact concrete raw materials include: 400 parts of silicate cement, 95 parts of silica fume, 370 parts of fine sand, 80 parts of steel fibers, 17 parts of water reducer, and 100 parts of water; the cross-linked modified heat-shrinkable fiber net is a hollow cylindrical structure obtained by blending polyester fiber and aramid fiber using a plain weave method (polyester fiber: aramid fiber = 1:2); the preparation method of the self-repairing anti-impact concrete includes the following steps:

[0073] 1) 400 parts of silicate cement, 95 parts of silica fume, 370 parts of fine sand, 80 parts of steel fiber and 12 parts of electromagnetic induction self-repairing fiber (accounting for 3% of the mass of cement) are mixed evenly, and then 100 parts of water and 17 parts of water reducing agent are added and mixed evenly, and stirred for 2 minutes to obtain abrasion-resistant concrete slurry;

[0074] 2) 60 parts of cross-linked modified heat-shrinkable fiber mesh (polyester fiber and aramid blended in a ratio of 1:2) are placed in the center of the cylindrical cavity mold. First, part of the impact-resistant concrete slurry is filled into the cylindrical fiber mesh (baffles are set on both sides). After the concrete inside is fixed, continue to pour and fill the entire mold. After forming, place it in a curing room for standard curing for 28 days (temperature 25°C, humidity 95%) to obtain self-repairing impact-resistant concrete based on heat-shrinkable fiber mesh and electromagnetic induction self-repairing fiber.

[0075] Comparative Example 1

[0076] A traditional abrasion-resistant concrete, the preparation method of which comprises the following steps:

[0077] 1) 400 parts of Portland cement, 95 parts of silica fume, 370 parts of fine sand and 80 parts of steel fiber were mixed evenly, and then 100 parts of water and 17 parts of water reducing agent were added and mixed evenly, and stirred for 2 minutes to obtain abrasion-resistant concrete slurry;

[0078] 2) pouring, molding and curing the obtained abrasion-resistant concrete slurry to obtain the abrasion-resistant concrete.

[0079] Comparative Example 2

[0080] A reinforced anti-abrasion concrete based on a cross-linked modified heat-shrinkable fiber mesh, the preparation method of which comprises the following steps: 1) mixing concrete slurry; 400 parts of silicate cement, 95 parts of silica fume, 370 parts of fine sand and 80 parts of steel fiber are mixed evenly, and then 100 parts of water and 17 parts of a water reducing agent are added and mixed evenly to obtain an anti-abrasion concrete slurry;

[0081] 2) 60 parts of a cross-linked modified heat-shrinkable fiber mesh (polyester fiber and aramid fiber blended in a ratio of 1:2; the preparation method is the same as in Example 1) are placed in the center of a cylindrical cavity mold, and first a portion of the anti-impact concrete slurry is filled into the cylindrical fiber mesh (baffles are set on both sides). After the concrete inside is formed, continue pouring to fill the entire mold. After forming, place it in a curing room for standard curing for 28 days (temperature 25°C, humidity 95%) to obtain a reinforced anti-impact concrete based on a cross-linked modified heat-shrinkable fiber mesh.

[0082] Comparative Example 3

[0083] A wear-resistant concrete based on electromagnetic induction self-repairing fiber, the preparation method of which comprises the following steps:

[0084] 1) 400 parts of silicate cement, 95 parts of silica fume, 370 parts of fine sand, 80 parts of steel fiber and 12 parts of electromagnetic induction self-repairing fiber (prepared by the same method as in Example 1) were mixed evenly, and then 100 parts of water and 17 parts of water reducing agent were added and mixed evenly, and stirred for 2 minutes to obtain an anti-abrasion concrete slurry;

[0085] 2) pouring and curing the concrete slurry to obtain electromagnetic induction self-repairing fiber anti-impact concrete.

[0086] Comparative Example 4

[0087] A method for preparing abrasion-resistant concrete based on hydrophilic modified composite chopped fibers and electromagnetic induction self-repairing fibers comprises the following steps:

[0088] 1) Mixing of concrete slurry: 400 parts of silicate cement, 95 parts of silica fume, 370 parts of fine sand, 80 parts of steel fiber and hydrophilically modified chopped fibers (including 20 parts of hydrophilically modified polyester and 40 parts of hydrophilically modified aramid chopped fibers) (length 3-12 mm), and 12 parts of electromagnetic induction self-repairing fibers (prepared by the same method as in Example 1) were mixed evenly, and then 100 parts of water and 17 parts of water reducing agent were added and mixed evenly to obtain abrasion-resistant concrete slurry;

[0089] 2) Filling part of the abrasion-resistant concrete slurry into a mold, curing after molding, and obtaining abrasion-resistant concrete based on hydrophilic modified chopped fibers and electromagnetic induction self-repairing fibers.

[0090] Comparative Example 5

[0091] A method for preparing abrasion-resistant concrete based on a heat-shrinkable fiber net and electromagnetic induction self-repairing fibers comprises the following steps:

[0092] 1) 400 parts of silicate cement, 95 parts of silica fume, 370 parts of fine sand, 80 parts of steel fiber and 12 parts of electromagnetic induction self-repairing fiber (accounting for 3% of the cement mass) are mixed evenly, and then 100 parts of water and 17 parts of water reducing agent are added and mixed evenly, and stirred for 2 minutes to obtain abrasion-resistant concrete slurry;

[0093] 2) 60 parts of heat-shrinkable fiber mesh (polyester fiber and aramid blended in a ratio of 1:2, prepared by the same method as in Example 1) are placed in the center of a cylindrical cavity mold. First, part of the impact-resistant concrete slurry is filled into the cylindrical fiber mesh (baffles are set on both sides). After the concrete inside is formed, continue to pour and fill the entire mold. After forming, place it in a curing room for standard curing for 28 days (temperature 25°C, humidity 95%) to obtain self-repairing impact-resistant concrete based on heat-shrinkable fiber mesh and electromagnetic induction self-repairing fiber; wherein the preparation method of the heat-shrinkable fiber mesh used is substantially the same as that in Example 1, the only difference being that no cross-linking modification is performed before blending and weaving.

[0094] The concrete obtained in Example 1 and Comparative Examples 1 to 5 were tested for mechanical properties and durability, and the results are shown in Table 4.

[0095] Table 5 Performance test results of concrete obtained from Example 1 and Comparative Examples 1 to 5 after curing for 28 days

[0096]

[0097] A self-healing experiment was conducted on the self-repairing anti-impact concrete based on the heat-shrinkable fiber net and the electromagnetic induction self-repairing fiber obtained in Example 1. The specific steps include:

[0098] Using the splitting test method, micro cracks are generated on the surface of the specimen. The specimen is immediately removed and the initial crack width is measured.

[0099] For the above concrete specimens, the temperature was raised to 200℃ and the magnetic field intensity was 0.3T to further observe the crack repair. The specific repair results are shown in Figure 2 It can be seen that the method of the present invention can realize self-repair of cracks with a width of 0.29 mm.

[0100] In order to verify the precise controlled release effect of the electromagnetic induction self-repairing fiber described in the present invention, by setting different magnetic field conditions such as magnetic field strength and action time, the release amount of the repair agent is measured by HPLC and other methods. With the increase of magnetic field strength and action time, the release amount of repair material (core material) in the microcapsule increases, the release is less at low magnetic field strength, and the cracks are effectively repaired at high magnetic field strength; different magnetic field frequencies lead to different release rates and patterns, low-frequency slow release is suitable for long-term repair, and high-frequency fast release is used for emergency treatment.

[0101] Embodiments 2 to 5

[0102] The preparation method of the self-healing and abrasion-resistant concrete described in Examples 2 to 5 is roughly the same as that in Example 1, except that the blending ratio of the fiber mesh and the electromagnetic induction self-healing fiber blending ratio (percentage of cement mass) are different. The performance test results of the fiber mesh, electromagnetic induction self-healing fiber and the obtained concrete after 28 days of curing are shown in Table 6 respectively.

[0103] Table 6 Performance test results of the fiber mesh-electromagnetic induction self-repairing fiber system and the obtained concrete used in Examples 2 to 4

[0104]

[0105]

[0106] Example 5

[0107] A self-repairing anti-abrasion concrete based on a heat-shrinkable fiber net and an electromagnetic induction self-repairing fiber (the specimen is in block form), wherein the components and their weight proportions include: 1062 parts of a self-repairing anti-abrasion concrete matrix raw material, 12 parts of an electromagnetic induction self-repairing fiber, and 60 parts of a cross-linked modified heat-shrinkable fiber net; wherein the self-repairing anti-abrasion concrete raw materials include: 400 parts of silicate cement, 95 parts of silica fume, 370 parts of fine sand, 80 parts of steel fiber, 17 parts of a water reducer, and 100 parts of water; the heat-shrinkable fiber net is obtained by weaving polyester fiber and aramid fiber in different blending ratios (see Table 7 for details) by plain weaving; the preparation method of the self-repairing anti-abrasion concrete includes the following steps:

[0108] 1) 400 parts of silicate cement, 95 parts of silica fume, 370 parts of fine sand, and 80 parts of steel fiber were mixed with different amounts of electromagnetic induction self-repairing fibers (see Table 7 for details), and then 100 parts of water and 17 parts of water reducer were added and mixed evenly, and stirred for 2 minutes to obtain abrasion-resistant concrete slurry;

[0109] 2) 60 portions of the heat-shrinkable fiber mesh were placed in the middle of the mold and the anti-impact concrete slurry was poured to fill the entire mold. After molding, the mold was placed in a curing room for 28 days (temperature 25°C, humidity 95%) to obtain self-repairing anti-impact concrete based on the heat-shrinkable fiber mesh and electromagnetic induction self-repairing fiber.

[0110] Table 7 Performance test results of different fiber mesh-electromagnetic induction self-repairing fiber systems and the resulting concrete in Example 6

[0111]

[0112] The above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A self-repairing anti-impact concrete based on heat-shrinkable fiber net and electromagnetic induction self-repairing fiber, characterized in that: It includes an impact-resistant concrete matrix and a cross-linked modified heat-shrinkable fiber net and an electromagnetic induction self-repairing fiber distributed inside it; wherein the heat-shrinkable fiber net is a fiber net that is woven and cross-linked modified by polyester fiber and aramid fiber in sequence; the electromagnetic induction self-repairing fiber includes a core material and a wall material, the core material includes methyl methacrylate and butyl acrylate, and the wall material includes polylactic acid and nano-Fe3O4.

2. The self-repairing and abrasion-resistant concrete according to claim 1, characterized in that: The raw materials and their weight proportions include: 1008-1140 parts of impact-resistant concrete matrix raw materials, 12-44 parts of electromagnetic induction self-repairing fibers, and 50-70 parts of cross-linked modified heat-shrinkable fiber nets.

3. The self-repairing and abrasion-resistant concrete according to claim 1 is characterized in that: The raw materials and their weight proportions in the anti-abrasion concrete matrix include: 400 parts of silicate cement, 78-110 parts of silica fume, 350-400 parts of fine sand, 70-90 parts of steel fiber, 15-20 parts of water reducer, and 95-120 parts of water.

4. The self-repairing and abrasion-resistant concrete according to claim 1, characterized in that: The cross-linking modification step is to use divinylbenzene to cross-link and modify the blended web of polyester fiber and aramid fiber.

5. The self-repairing and abrasion-resistant concrete according to claim 1, characterized in that: The electromagnetic induction self-repairing fiber has an average diameter of 0.2 to 2 μm, an average capsule wall thickness of 50 to 300 nm, and a length of 250 to 4000 μm.

6. The self-repairing and abrasion-resistant concrete according to claim 1, characterized in that: The electromagnetic induction self-repairing fiber is firstly cross-linked with methyl methacrylate and butyl acrylate to obtain a composite core material, which is then mixed with a polylactic acid solution and ferrosoferric oxide nanoparticles to prepare a spinning solution, and then electrostatic spinning is performed to obtain the composite core material.

7. The self-repairing and abrasion-resistant concrete according to claim 1 is characterized in that: The mass ratio of methyl methacrylate, butyl acrylate, polylactic acid and ferrosoferric oxide nanoparticles introduced is 1:(0.25-1):(0.1-0.3):(0.025-0.15).

8. The self-repairing and abrasion-resistant concrete according to claim 1, characterized in that: The silicate cement is one of P·I52.5 and P·Ⅱ52.5; the content of SiO2 in the silica fume is ≥92%, and the particle size is 0.1-0.3μm; the fine sand is one of natural sand and quartz sand, and the particle size of the fine sand is 0.075-0.6mm; the steel fiber is copper-plated steel fiber, the length is 12-13mm, and the diameter is 0.18-0.23mm.

9. The self-repairing and abrasion-resistant concrete according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid water reducing agent, and the water reducing rate is ≥25%.

10. The method for preparing the self-repairing anti-abrasion concrete based on the heat-shrinkable fiber net and the electromagnetic induction self-repairing fiber according to any one of claims 1 to 9, characterized in that: The following steps are involved: 1) The cross-linked modified heat shrinkable fiber mesh is arranged in the middle of the mold according to the structural requirements of the impact-resistant concrete; 2) preparing a slurry of an anti-impact concrete matrix according to a proportion, and then adding the electromagnetic induction self-repairing fiber into the obtained slurry and stirring it evenly; 3) pouring the obtained mixture into a mold provided with a cross-linked modified heat shrinkable fiber mesh, forming, and curing to obtain the self-repairing anti-impact concrete.

Citation Information

Patent Citations

  • Electromagnetic controlled-release microcapsule / steel fiber self-repairing concrete and preparation method thereof

    CN111393063A

  • Preparation method of intelligent self-healing admixture

    CN112358218A

  • Thermal shrinkage type fiber reinforced concrete

    CN114477820A

  • Blend fiber and nested microcapsule self-repairing concrete and preparation method thereof

    CN118724525A

  • Anti-abrasion concrete and application thereof

    CN118724535A